IMPROVING THE TASTE PROPERTIES OF MEDICINAL FORMS IN ORAL DISEASES, PARTICULARLY IN CASES OF STOMATITIS AND ULCERS (Uzbekistan Open Conference, 2026)
The article discusses the etiology, pathogenesis, and clinical manifestations of stomatitis and oral ulcers, as well as modern treatment methods. Issues of safety, contraindications, and expected therapeutic outcomes are analyzed. Data that may serve as a basis for further clinical research are provided. In addition, a practical protocol for local treatment is presented. The advantages of rinsing the oral cavity with an antiseptic, using benzocaine for pain relief, and applying sea buckthorn oil are highlighted.